Growth and development in children with classic congenital adrenal hyperplasia. Issue 1 (February 2017) - Bonfig, Walter
Abstract : Purpose of review: Final height outcome in classic congenital adrenal hyperplasia (CAH) has been of interest for many years. With analysis of growth patterns and used glucocorticoid regimens, enhanced treatment strategies have been developed and are still under development. Recent findings: Most of the current reports on final height outcome are confirmative of previous results. Final height data is still reported in cohorts that were diagnosed clinically and not by newborn screening. Clinical diagnosis of CAH leads to delayed diagnosis especially of simple virilizing CAH with significantly advanced bone age resulting in early pubertal development and reduced final height. In contrast salt-wasting CAH is diagnosed at an earlier stage in most cases resulting in better final height outcome in some cohorts. Nevertheless, final height outcome in patients with CAH treated with glucocorticoids is lower than the population norm and also at the lower end of genetic potential. Summary: Achievement of regular adult height is still a challenge with conventional glucocorticoid treatment in patients with CAH, which is why new hydrocortisone formulations and new treatment options for CAH are underway.